Etiological spectrum and short-term outcomes of acute kidney injury in hospitalised patients of uncertain aetiology who underwent percutaneous renal biopsy - Qazi Muhammad Huzaifa; Tabassum Elahi; Sunbal Jahangir; Kalimullah Khan; Irum Memon (Journal of the Pakistan Medical Association, 2025)
Objective: To analyse the aetiological spectrum, clinical presentation and short-term renal outcomes of patients withacute kidney injury of uncertain aetiology subjected to percutaneous renal biopsy. Method: The prospective, cohort study was conducted at the Sindh Institute of Urology and Transplantation, Karachi,from March 1 to October 30, 2024, and comprised hospitalised acute kidney injury patients of either gender aged 18-75 years who had been subjected to percutaneous renal biopsy. The patients were followed up for at least threemonths from the time of the biopsy. Data was analysed using SPSS 26. Results: Of the 115 patients with mean age 32.61±10.20 years, 60(52.2%) were females and 55(47.8%) were males.The mean estimated glomerular filtration rate was 23.05±18.62ml/min/1.73m². Over half 62 (53.9%) required kidneyreplacement therapy at presentation. Most patients 104(90.4%) had renal involvement due to glomerulopathy, whilethe rest exhibited non-glomerular renal disease. The most common primary glomerular diseases were focal segmentalglomerulosclerosis 26(22.6%), membranoproliferative glomerulonephritis 16(13.9%) and membranousnephropathy 4(3.5%). The leading secondary glomerular diseases were pauci-immune necrotising glomerulonephritis18(15.7%), thrombotic microangiopathy 16(13.9%) and lupus nephritis 8(7.0%). At 3-month follow-up, 43(37.4%)achieved complete recovery, 34(29.6%) achieved partial recovery and 38(33%) showed no recovery, while 4(3.4%)patients from the no recovery group expired at the time of the last follow-up. Patients who required kidneyreplacement therapy on admission had lower rates of complete recovery (p <0.001), with more patients progressingto end-stage kidney disease (p=0.02) and increased mortality (p=0.08). Conclusion: Most biopsied acute kidney injury patients had coexisting glomerular disease with worse renal recovery,while acute tubular necrosis alone was less frequent. Keywords: Acute kidney injury, End-stage kidney disease, Glomerular diseases, Kidney replacement therapy,Percutaneous renal biopsy.